2008
DOI: 10.1088/0004-6256/135/5/1968
|View full text |Cite
|
Sign up to set email alerts
|

WEIGHING THE BLACK HOLES INz≈ 2 SUBMILLIMETER-EMITTING GALAXIES HOSTING ACTIVE GALACTIC NUCLEI

Abstract: We place direct observational constraints on the black-hole masses (M BH ) of the cosmologically important z ≈ 2 submillimeter-emitting galaxy (SMG; f 850 µm 4 mJy) population, and use measured host-galaxy masses to explore their evolutionary status. We employ the well-established virial black-hole mass estimator to "weigh" the black holes of a sample of z ≈ 2 SMGs which exhibit broad Hα or Hβ emission. We find that the average black-hole mass and Eddington ratio (η = L bol /L Edd ) of the lower-luminosity bro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
178
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(208 citation statements)
references
References 168 publications
(375 reference statements)
26
178
4
Order By: Relevance
“…These are consistent with the local relationship ( M BH /M bulge ∼ 0.0014; Häring & Rix 2004;Marconi & Hunt 2003), and also with the ratios measured in type I QSOs (0.007±0.003; Peng et al 2006), but larger than those estimated in SMGs (0.0001-0.0008; Alexander et al 2008). Several recent models of galaxy evolution postulate that only relatively evolved supermassive black holes may be able to affect their surrounding gas (Churazov et al 2005;Merloni & Heinz 2008;Fanidakis et al 2011).…”
Section: Evolutionary Phasesupporting
confidence: 89%
See 1 more Smart Citation
“…These are consistent with the local relationship ( M BH /M bulge ∼ 0.0014; Häring & Rix 2004;Marconi & Hunt 2003), and also with the ratios measured in type I QSOs (0.007±0.003; Peng et al 2006), but larger than those estimated in SMGs (0.0001-0.0008; Alexander et al 2008). Several recent models of galaxy evolution postulate that only relatively evolved supermassive black holes may be able to affect their surrounding gas (Churazov et al 2005;Merloni & Heinz 2008;Fanidakis et al 2011).…”
Section: Evolutionary Phasesupporting
confidence: 89%
“…Under the assumption that the gas is driven by gravity and is approximately virialized, CO line profiles and velocity gradients can be used to estimate dynamical masses. In recent years, CO observations have led to a plethora of new constraints, e.g., on star-formation efficiencies in different types of high-z galaxies (Greve et al 2005;Solomon & Vanden Bout 2005;Tacconi et al 2008;Coppin et al 2008;Iono et al 2009;Daddi et al 2010;Riechers 2011), the regulation of star-formation in the most rapidly growing galaxies (Beelen et al 2004;Greve et al 2005;Daddi et al 2008;Schinnerer et al 2008;Nesvadba et al 2009;Genzel et al 2010), or the co-evolution of black holes and their host galaxies (Peng et al 2006;Maiolino et al 2007;Alexander et al 2008;Riechers et al 2009b;Wang et al 2010). …”
Section: Introductionmentioning
confidence: 99%
“…At right, the measured black-hole to host galaxy mass ratio measured in SMGs against other galaxy populations. This figure is reproduced from Alexander et al (2008) with permission from the authors and AAS. The local relationship is given by the dashed line (Häring & Rix, 2004), whereas the measurement for radio-selected AGN between 0 < z < 2 is shown in dark gray (McLure et al, 2006) and z > 2 quasars in light gray (Peng et al, 2006).…”
Section: Agn Contentmentioning
confidence: 99%
“…The Wang et al (2013a) work is of particular note since its sample is the ∼100 ALMA-confirmed 870µm-selected sources in CDFS with unambiguous counterparts, enabling effectively more precise measurements in both X-ray and FIR. An important follow-up to these X-ray studies of SMGs came in Alexander et al (2008). Alexander et al place observational constraints on central black-hole masses for SMGs using Hα (or Hβ) line analysis in addition to the X-rays.…”
Section: Agn Contentmentioning
confidence: 99%
“…The origin of broad (FWHM 1000 km s −1 ) Hα line emission at high redshift has either been attributed to winds driven by starbursts (e.g., Le Tiran et al 2011;Shapiro et al 2009;Nesvadba et al 2007) or active galactic nuclei on galaxywide scales (e.g., Alexander et al 2010;Nesvadba et al 2011b;Harrison et al 2012), or alternatively, to gas motions in the deep gravitational potential wells very near the supermassive black hole (e.g., Alexander et al 2008;Coppin et al 2008;Nesvadba et al 2011b). For galaxies like NVSS J234235−384526, and perhaps NVSS J002431−303330 and NVSS J004000−303333, which only have relatively broad [OIII] components, it is clear that the broad-line emission probes gas in the narrow-line region or outside, at larger galactocentric radii.…”
Section: Broad-line Components and Properties Of Black Holesmentioning
confidence: 99%